Hakim Ad Hoc Pada Penyelesaian Perkara Lingkungan Hidup Dalam Sistem Peradilan Di Indonesia - Novita Endah Lestari (Scholar Center, 2022)
This study aims to examine the concept of ad hoc judges in environmental courts. This research is normative legal research, the nature of prescriptive research. The results of this study indicate that environmental cases resolved in general courts have not been able to provide ecological justice and instead have resulted in decisions that are not in favor of the environment. The role of judges is necessary to protect human or non-human (environmental) interests that are violated. In protecting human and non-human (environmental) interests that are violated. Having an ad hoc environmental judge who understands environmental issues is expected to be able to give a fair and wise decision.